KEKUATAN BUKTI ILMIAH PADA TINDAK PIDANA KEBAKARAN HUTAN DAN LAHAN DALAM RANGKA PENEGAKAN HUKUM PIDANA LINGKUNGAN HIDUP DI PROVINSI RIAU - Ismaeri, Randy; Jayakusuma, Zulfikar; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Forests as one of the natural resources with great potential to be used to improve community welfare. Because of the importance of the function of forests for human life so that the preservation of the forest needs to be maintained so that the forest needs to be maintained so that the forest does not lose its function. Things that can cause disruption of forest functions include forest fires. One of the cases of forest fires which was acquitted with the defendant PT. Adei Plantation and Industry, while scientific evidence presented in court shows that PT. Adei Plantation and Industry intentionally committed acts resulting in exceedance of ambient air quality books, water quality standards, sea water quality standards or environmental damage and human safety hazards and resulting in significant injury or death to people who could be convicted and receive strict sanctions.This type of research is normative legal research that is the principles of law. The legal principle that is the object of the problem in research is the principle contained in the criminal justice system, that a judge must be able to consider the facts of the trial to create a sense of justice. While judging from the nature of this research, it is descriptive. This study uses secondary data that is ready-made data.The results of this study are an analysis of judges' legal considerations in dropping criminal case decisions No. 228 / Pid.Sus / 2013 / PN.Plw is a consideration of the Decision of the First Level Judge, then Article 99 paragraph (1) jo article 116 paragraph (1) letter (a) ) RI Law. Number 32 of 2009 concerning Environmental Protection and Management in conjunction with Law Number 14 of 1970 in conjunction with Law Number 48 of 2009 concerning Judicial Power, Law Number 8 of 1981 concerning KUHAP and other regulations relating to this case. . The criminal conviction of the defendant by the Pelalawan District Court at the first instance and the Pekanbaru High Court at the appeal level were too mild. The defendant's actions are not in line with the government's program which must run environmentally friendly business activities.Keywords: Law Enforcement, Pharmaceutical Supply Dealers, No Licens